Theory of Manu and human qualities in every age according to the Upanishad and Purana literature - Diah, Ni Kadek Berliana (Life and Death: Journal of Eschatology, 2024)
Intelligent beings, often referred to as atma or spirit, are described as "atma" in the Upanishads, or as Brahman. Brahman represents the principle of the universe. Seeking guidance, humans turn to the words of God found in the Puranas and Upanishads. The concept of the manu theory and human qualities in different eras is prevalent in Vedic literature. The Puranas and Upanishads contain a section dedicated to the theory of manu and human qualities for each era. The Puranas hold a significant and strategic position in the hierarchy of the Vedas and Hindu Literature. This research aims to analyze the Manu Theory and human qualities of each era as described in Purana and Upanishad literature using qualitative descriptive research methods. The findings of this research reveal that the concept of manu theory and human qualities, as depicted in Purana and Upanishad literature, reflects Hindus' pride and increasing belief in the teachings of Hinduism as a suitable guide for navigating life in this world and the natural environment.